2021
DOI: 10.1021/acsapm.0c01230
|View full text |Cite
|
Sign up to set email alerts
|

Robust Hilly Polyamide Membrane for Fast Desalination

Abstract: Tailoring the microstructure of a selective layer is a highly attractive way to improve the water flux of a reverse osmosis (RO) membrane by forming a crumpled surface without altering its chemical structure required for high salt rejection. However, it is challenging to maintain its structural integrity and stability and high flux at high pressure during desalination. Herein, a robust hilly thin-film composite (TFC) polyamide (PA) membrane is developed based on composite substrates made of cellulose nanofiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As expected, the zeta potential of the membrane gradually increased, indicating a higher surface charge for M-0.15 and M-0.2, which could be attributed to the presence of higher nanozeolites, particularly on the surface of the support layer. On the other hand, the presence of nanozeolite beneath the PA layer might also contribute to additional rejection by size exclusion [ 68 ]. Although Y-type zeolites are characterized by pores in a range of 0.74 nm, which is significantly higher than the size of monovalent salts, studies have reported that faujasite structure can effectively filter hydrated Na + ions.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the zeta potential of the membrane gradually increased, indicating a higher surface charge for M-0.15 and M-0.2, which could be attributed to the presence of higher nanozeolites, particularly on the surface of the support layer. On the other hand, the presence of nanozeolite beneath the PA layer might also contribute to additional rejection by size exclusion [ 68 ]. Although Y-type zeolites are characterized by pores in a range of 0.74 nm, which is significantly higher than the size of monovalent salts, studies have reported that faujasite structure can effectively filter hydrated Na + ions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a rough TFC polyamide (PA) membrane formed by NH 2 -MIL-53(Al) incorporation exhibited an excellent water permeability of 5.55 L mA h bar −1 . 173 The UiO-66-NH 2 TFN membrane showed an increased pure water permeability by 50%. 174 In addition, the incorporation of reticular materials may bring about more benefits.…”
Section: Membrane Separation For Treating Pollutionmentioning
confidence: 97%
“…Cellulose fiber with excellent hydrophilicity, wide variety of sources and low cost has been widely applied in membrane fabrication for heavy metal removal and water purification 108 . Cellulose nanofibers (CNF), sulfonated cellulose nanofibers and bacterial cellulose nanofibers were used for intermediate to improve TFC membrane structure and performance 109–111 . Low et al 109 fabricated a TFC membrane by vacuum filtration CNF and NH 2 ‐MIL‐53 (Al) MOF nanoparticles on the Nylon substrate as support for IP procedure.…”
Section: Construction Strategies Of Crumpled Structure Membranementioning
confidence: 99%
“…108 Cellulose nanofibers (CNF), sulfonated cellulose nanofibers and bacterial cellulose nanofibers were used for intermediate to improve TFC membrane structure and performance. [109][110][111] Low et al 109 fabricated a TFC membrane by vacuum filtration CNF and NH 2 -MIL-53 (Al) MOF nanoparticles on the Nylon substrate as support for IP procedure. The hydrophilic nanofiber provided highly porous substrate and MOF created hilly surface morphology.…”
Section: Construction Of Functional Interlayermentioning
confidence: 99%